PENGARUH RETURN ON ASSET, EARNING PER SHARE, DAN PRICE EARNING RATIO TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - BLONGKOD, ASTRID RAVITASARI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
The study intends to determine simultaneous and partial influence of Return On Asset (X1), Earning Per Share (X2) and Price Earning Ratio (X3) on return share of manufacturing company sub sector cigarettes industry listed on Indonesia Stock Exchange. Data used is secondary data that is gathered from Indonesia Stock Exchange Website. Technique of data analysis is multiple linear regressions, which is proceeded with E-Views program version 9. The result of study confirms that partially, Return On Asset (ROA) and Price Earning Ratio (PER) have non-significant influence on Return Share in manufacturing company sub sector cigarrettes industry listed on Indonesia Stock Exchange during the period of 2012-2016 while Earning Per Share (EPS) has significant influence on Return Share. Simultaneously, Return On Asset (ROA), Earning Per Share (EPS), and Price Earning Ratio (PER) show significant influence on Return Share in manufacturing company sub sector cigarrettes industry listed on Indonesia Stock Exchange in the period of 2012-2016 by 20,2328%.